Portlandia. Season seven [videorecording (DVD)] - Krisel, Jonathan; Armisen, Fred, 1966-; Brownstein, Carrie, 1974- (MVD Entertainment Group., 2017)
The hit sketch comedy driven by a series of hilarious character-based shorts all of which take place in the creators' dreamy and absurd rendering of Portland, Oregon--where '90s culture reigns supreme and political correctness is all the rage.